ILRI extends bandwidth and use of ICTs for collaboration and communication - Moore, I. (International Livestock Research Institute, 2011)
Speaking at the January 2011 ILRI Partnerships and Communications (P&C) retreat, Iam Moore, Head of ICT at ILRI reflects on the past year. He points to improvements in connectivity and bandwidth at various ILRI locations, especially at the ILRI campus in Addis Ababa. Much progress has also been made in the use of ICTs to support collaboration and communication among scientists and alongside events. For 2011, we need to extend our efforts to widen awareness of these tools.